POSTGRESQL DATABASES SECURITY CONFIGURATION CHECKLIST - Gudriks, Rinalds; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
The paper provides PostgreSQL configuration checklist to make databases safer. The main part describes with examples about vulnerabilities and how to solve them.